Study the Effect of Local vs. Imported Heavy and Light Turkey Strains on Muscles and Bones Conformation of the Drum-Sticks - Taha, Nazar T. (International Journal of Poultry Science, 2012)
The Experiment was conducted at the Laboratories of Animal Resources Department, College Agriculture and Forestry, Mosul University, using drum-stick part of a slaughtered body of local Iraqi and imported American Heavy and Light of drum-sticks Turkey bird’s strains. Anatomies of each drum-stick were done to study muscles and bones conformations such as weight, length, width and thickness of muscles and weight, length, width and thickness of the dressed drum-sticks bones (Nazarian bones). The results yielded highly significant (p<0.01) strain differences in drum-stick weight, width and thickness for the heavy vs. light and local strains, which reflected the same results on the same traits of flesh dressed meat of the drum-sticks and on tibia, fibula and Nazarian bones traits also. Number of muscles and Nazarian bones in the three strains showed highly significant (p<0.01) differences (14, 7 and 9) muscles between the local vs. light and heavy strains and (18, 10 and 16) bone for the local vs. light but not with Heavy strains. The results of the present study revealed that the Nazarian bone shapes showed different bone shapes, some of them were replicated in the three different strains.